Testing Pair-Wise Convergence of Western Balkan and European union Countries - Duro, Enton; Kokaveshi, Ergita; Muço, Klodian (European Journal of Sustainable Development, 2023)
The present research performs the GDP per capita convergence analyses of Western Balkan (WB) countries to European Union (EU) countries. There are few testing convergence methods based on theoretical insights on the neoclassical model, however pairwise convergence method doesn’t seem usually applied in the case of WB and EU countries. The test of convergence hypothesis in this research is based on the GDP per capita’s data, constant 2017 international in PPP terms, made available by the World Bank. The pairwise convergence test suggested here can be considered as an extension of Webber and While (2003, 2004, 2009) methodology. The outcomes have been compared to Bernard, Durlauf (1995) and Pesaran (2006) methodology of the pairwise convergence, by adapting ADF time series tests of the stationarity. In conclusion, despite to the controversy of one pair case, the comparative process of both methods seems to be aligned. However, further investigation needs to be performed to confirm the effectiveness and efficiency of this suggestion. Keywords: GDP per capita, pairwise convergence, Western Ballkan countries, methodology